PENGUKURAN TEKANAN DARAH PADA PASIEN PESERTA JKN DENGAN PENYAKIT JANTUNG ISKEMIK DI INSTALASI RAWAT JALAN RUMAH SAKIT ST. ELISABETH SEMARANG - Fef Rukminingsih; Nike Kusuma Dewi (Jurnal Insan Farmasi Indonesia, 2020)
Ischemic heart disease (IHD) is defined as a lack of oxygen and decreased or absent blood flow to the myocardium caused by narrowing of the coronary arteries. Hypertension is a risk factor that plays an important role in IHD. Hypertension therapy in IHD patients aims to prevent death, myocardial infarction. This study aims to evaluate the achievement of blood pressure targets in IHD patients participating in JKN in the outpatient installation of St. Elisabeth Hospital Semarang. This research is a descriptive observational study using retrospective data. Data obtained from the medical records. The inclusion criteria were JKN participant patients with IHD in the Outpatient Installation of St. Elisabeth Hospital Semarang for the period of October-December 2019 who received antihypertensive, aged 26-65 years, had blood pressure data for two consecutive months. The results were 88 patients, consisting of 64 (72.73%) male patients, 46 (52.27%) patients aged 56-65 years. 57 (64.78%) patients had comorbidities, the most comorbidities were type 2 diabetes. The most widely used antihypertensive agents were beta blockers. A total of 82 (93.18%) patients reached the target blood pressure based on JNC 8. The greater the success in achieving the therapeutic target, the risk of death from IHD will decrease.